A cross-cultural study of children's drawings and parents' attitudes about peace and war - Frias, Larissa V. (Ann Arbor Michigan ProQuest LLC, 2009)
The goals of this study were to describe how children from different cultural backgrounds represent peace and war in their drawings and verbal descriptions and to study its association with their parents' attitudes towards the concepts. Thirty eight (38) U.S., South Korean, and Filipino-immigrant parent-child dyads participated in the study. Children who were 8-13 years old drew and verbally described pictures of peace and war. One parent of each child was asked to complete the Hawk/Dove Attitude Scale. Guided by the symbolic interactionism framework, themes and overarching categories of the drawings were established through coding the images and the narratives while attitude scores of the parents were grouped into Dove (leaning towards the peace direction), Moderate, and Hawk (leaning towards the war direction). Findings showed nineteen peace themes in children's drawings and narratives organized into 7 overarching categories: negative peace, people involved in peace, non-human images, positive feelings, state of quietness, positive social actions and interactions, and beauty. There were seventeen war themes with seven overarching categories that included aggressive actions, consequences of war, negative feelings, concrete objects, conflict, people involved in war, and natural phenomena. Some themes were associated with cultural practices, values, and contextual events. In addition, peace themes were more frequently found in drawings of children of Dove parents compared to the drawings of children of Hawk parents. On the other hand, war themes were more frequent in drawings of children of Hawk parents. Implications for research and practice were discussed especially in the area of peace education.--Abstract.
Thesis (Ph.D.)--Purdue University, 2008.
Keywords: Children's drawings; Drawing, Psychology of